Calculation of joints of bending wooden structural elements in ANSYS Workbench (Международный научный журнал «Инженер», 2026)
The article highlights the increase of joint strength in the joints of bending wooden elements, the results and indicators of theoretical calculations obtained with the help of ANSYS Workbench computer program on stress-strain states of joints of wooden structures.